COMPUTED TOMOGRAPHIC CHARACTERISTICS OF THE THYROID GLANDS IN EIGHT HYPERTHYROID CATS PRE‐ AND POSTMETHIMAZOLE TREATMENT COMPARED WITH SEVEN EUTHYROID CATS. Issue 2 (5th December 2016) - Bush, Jennifer L.; Nemanic, Sarah; Gordon, Jana; Bobe, Gerd
Abstract : Hyperthyroidism is the most common feline endocrinopathy; thyroid computed tomography (CT) may improve disease detection and methimazole dose selection. Objectives of this experimental pre‐post with historical case‐control study were to perform thyroid CT imaging in awake or mildly sedated hyperthyroid cats, compare thyroid gland CT appearance in euthyroid and hyperthyroid cats pre‐ and postmethimazole treatment, and determine whether thyroid size or attenuation correlate with methimazole dose needed for euthyroidism. Premethimazole treatment, eight hyperthyroid cats received CT scans from the head to heart, which were compared to CT of seven euthyroid cats. Total thyroxine levels were monitored every 3–4 weeks. Postmethimazole CT was performed 30 days after achieving euthyroid status. Computed tomography parameters recorded included thyroid length, width, height, attenuation, and heterogeneity. Median time between CT was 70 days (53–213 days). Mild sedation was needed in five hyperthyroid cats premethimazole, and none postmethimazole. Thyroid volume was significantly larger in hyperthyroid cats compared to euthyroid cats (785.0 mm 3 vs. 154.9 mm 3 ; P = 0.002) and remained unchanged by methimazole treatment (−4.5 mm3; P = 0.50). Thyroid attenuation and heterogeneity decreased with methimazole treatment (96.1 HU vs. 85.9 HU; P = 0.02. 12.4 HU vs. 8.1 HU; P = 0.009). Methimazole dose ranged from 2.5 to 10 mg daily with a positive correlation between pretreatment thyroid gland volume and dose needed to achieve euthyroidism ( P = 0.03). Euthyroid and hyperthyroid cats are easily imaged awake or mildly sedated with CT. Methimazole in hyperthyroid cats significantly lowers thyroid attenuation and heterogeneity, but not size.